Influence of dynamic properties of the process module on vertical vibrations of the wheel axis - Yuri P. Kornyushin; Maksim V. Sidorov (International Journal of Advanced Studies)
Background. The article examines the influence of the dynamic properties of the technological module on the process of forming vertical vibrations of the wheel axis when moving along a given bearing surface. The following methods were used in the study: a mathematical model of half of the technological module, a bus model. The amplitude-frequency characteristics of the system and spectral densities for vertical displacement and acceleration of the wheel axis for four configurations are obtained when changing the parameter characterizing the dynamic properties of technological modules. Statistical dynamics methods were used to analyze the dependencies. With an increase in the mass of the technological module from 1429 kg to 3929 kg (to transfer the tractor from traction class 1.4 to traction class 2 and 3, respectively), when using 15.5R38 tires, there is a decrease in the natural frequency of the technological module from 24 to 14 rad/s and an increase in the maximum spectral density from 0.5*10-3 to 4*10-3. With an increase in the mass of the technological module from 2343 kg to 4847 kg (to transfer the tractor from traction class 3 to traction class 4 and 5, respectively), when using tires 21.3R24, there is a decrease in the natural oscillation frequency of the technological module from 18 to 12 rad/s and an increase in the maximum spectral density from 1.5 * 10-3 to 6*10-3. The spectral density (characterizing the distribution of process energy) of vertical vibrations of the support surface in the frequency range (0...5 rad/s) coincides with the spectral density of the wheel axis of technological modules of all configurations.